Shoulder injuries in provincial male fast bowlers - predisposing factors - Aginsky, KD; Lategan, L; Stretch, RA (South African Journal of Sports Medicine, 2004)
Objectives. To investigate the relationship between shoulder flexibility and isokinetic strength as possible factors that may predispose provincial fast bowlers to shoulder injuries. Design. Twenty-one players, 12 of whom had no history of shoulder injuries and 9 of whom had experienced a shoulder injury to the bowling arm, were assessed for shoulder strength using a Cybex Norm isokinetic dynamometer. Absolute and relative peak torque measures were obtained at isokinetic speeds of 90°/s and 180°/s, with both concentric and eccentric contractions performed. Shoulder flexibility was tested using a Leighton Flexometer in both internal and external shoulder rotation. The players were classified into a front-on (N = 7), semi front-on (N = 7) or side-on (N = 7) bowling action from video footage recorded after a bowling trial in the nets. Results. Shoulder injuries were more common in fast bowlers with a front-on action (N = 5) than the bowlers with a side-on (N = 2) or semi front-on (N = 2) action. Sixteen of the 21 fast bowlers showed low stability ratios compared with gravity corrected functional ratios, indicating an imbalance and the presence of possible dysfunction. The injured group of fast bowlers showed higher concentric weight-normalised torque values for internal rotation at the higher velocity (180°/s) (65.20 ± 10.03 vs. 45.91 ± 10.26 Nm.kg-1 p < 0.009: injured vs. uninjured), which would suggest greater instability when compared with the uninjured players. This imbalance could indicate the presence of a predisposition to impingement syndrome in the injured subjects. There was an increase in the external rotation ranges of movement for both groups, indicating a degree of hypermobility in both groups. The results indicate that the presence of possible dysfunction in the shoulder rotators, combined with a front-on bowling action and external rotation hypermobility, are possible predisposing factors for chronic shoulder injuries in cricket fast bowlers. South African Journal of Sports Medicine Vol.16(1) 2004: 25-28